The research landscape of rural sustainable livelihood: a scientometric analysis - Amaliah, Yusriah; Husni, A. Hasyim Asyari Amir; Ansar, Muhammad Chaeroel; Chowdhury, Kuntala (Frontiers in Sustainability, 2025)
IntroductionThe issue of rural sustainable livelihoods has gained significant academic attention due to global concerns such as poverty, climate change, and rural development disparities. Despite a growing body of literature, a comprehensive mapping of this field’s intellectual landscape is still lacking.MethodsThis study employed a scientometric approach using CiteSpace software to analyze 1,141 articles indexed in Scopus from 1988 to 2023. The analysis included citation patterns, co-authorship networks, co-citation structures, and keyword co-occurrence to examine research evolution, key contributors, and collaboration intensity.ResultsThe research trend followed four phases: preparation, initial growth, rapid expansion, and stabilization. The field is highly interdisciplinary, bridging environmental sciences, social sciences, and economics. However, author, institutional, and international collaborations remain sparse. China, India, and South Africa were identified as leading contributors, while dominant themes included climate change adaptation, sustainable livelihood frameworks, and social capital.DiscussionThe results highlight the fragmented nature of research networks and the need for greater cross-disciplinary and cross-regional collaboration. Future research should address thematic gaps such as gender equality and digital innovation in rural development. This study offers critical insights for shaping integrative and policy-relevant strategies for sustainable rural livelihoods.